A block-coupled Finite Volume methodology for linear elasticity and unstructured meshes. (15th October 2016) - Cardiff, P.; Tuković, Ž.; Jasak, H.; Ivanković, A.
Highlights: A coupled extended-stencil cell-centred Finite Volume solution methodology is proposed. Face tangential gradients of displacement are implicitly calculated using a Finite Area method. Non-orthogonal corrections terms are treated in a fully implicit coupled manner. In cases examined, the method is faster than comparable Finite Element and Finite Volume methods. Abstract: The current article presents a fully coupled cell-centred Finite Volume solution methodology for linear elasticity and unstructured meshes. Details are given of the novel implicit discretisation and block coupled solution procedure, including use of a Finite Area method for face tangential gradient calculations and coupled treatment of non-orthogonal corrections. A number of 2-D and 3-D linear-elastic benchmark test cases are examined using hexahedral, tetrahedral and general polyhedral meshes; solution accuracy and efficiency are compared with that of a segregated procedure and a commercial Finite Element software, where the new method is shown to be faster in all cases.